The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1984-82502009000200017
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of different doses of cyclophosphamide on the reproductive parameters of male mice

Abstract: The cyclophosphamide is used in cancer treatment. The aim of this study was evaluating the effect of different doses of this drug on male mice reproductive parameters. The cyclophosphamide was administered in the doses 100, 150, 200 e 250 mg.kg -1 , intraperitoneal route, for six weeks. As a result, it was observed a decrease in body mass and a decrease in testicles and kidney's weight, in all animals treated with cyclophosphamide. Only the groups that received the doses 100, 150 mg.kg -1 of cyclophosphamide w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 25 publications
(25 reference statements)
5
12
0
2
Order By: Relevance
“…Figures 3c and 4c), there was minimal swelling and cellular debris; and the duct epithelium and cells were better preserved, compared to the cyclophosphamide-only group. There was also loss of interstitial space between In this study, administration of cyclophosphamide was associated with significant weight loss, which is consistent with reports of previous studies in rodents (Kanno, Sensiate, Aparecida de Paula, & Salles, 2009;Kumar, Singh, & Reddy, 2013;Latha & Panikkar, 1999;Myers et al, 2017). In the group where Maca alone was administered at 500 mg/kg (Figures 3e and 4e), there was an increase in sperm concentration within the ducts; duct epithelium and cells were normal and well preserved.…”
Section: Effect Of Maca On Latency To Achieve Pregnancy and Litter supporting
confidence: 91%
“…Figures 3c and 4c), there was minimal swelling and cellular debris; and the duct epithelium and cells were better preserved, compared to the cyclophosphamide-only group. There was also loss of interstitial space between In this study, administration of cyclophosphamide was associated with significant weight loss, which is consistent with reports of previous studies in rodents (Kanno, Sensiate, Aparecida de Paula, & Salles, 2009;Kumar, Singh, & Reddy, 2013;Latha & Panikkar, 1999;Myers et al, 2017). In the group where Maca alone was administered at 500 mg/kg (Figures 3e and 4e), there was an increase in sperm concentration within the ducts; duct epithelium and cells were normal and well preserved.…”
Section: Effect Of Maca On Latency To Achieve Pregnancy and Litter supporting
confidence: 91%
“…These results have been confirmed by previous studies [1,14], in which a significant reduction in the weight of the testes following CP treatment has been reported. These results have been confirmed by previous studies [1,14], in which a significant reduction in the weight of the testes following CP treatment has been reported.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies on male rats have confirmed that the administration of CP resulted in oligospermia, azoospermia, and histological alterations in the testes [1,13,14]. A wide range of adverse effects including reproductive toxicity have been found following CP treatment in humans and experimental animals.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Este é um substrato da enzima aldeído desidrogenase e, em células que contém esta enzima, a maior parte do 4-HOCy é oxidado a carboxifosfamida (um agente citotóxico) e excretado na urina. Consequentemente, células contendo elevada concentração de aldeído desidrogenase são resistentes aos metabólitos da ciclofosfamida (DeVITA; HELLMAN;ROSENBERG, 2000;JENSEN et al, 2008;KANNO et al, 2009) .…”
Section: Ciclofosfamidaunclassified